Efektivitas Edukasi Digital dalam Meningkatkan Kesiapan dan Keselamatan Pasien Perioperatif: Literature Review - Tri Wahyuni Ismoyowati; Muhamad Arief Fadli; Sahat Tumpal Salomo; Henry Agus Agus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The perioperative period is a critical phase that requires optimal patient preparation to improve surgical outcomes and ensure patient safety. Inadequate patient knowledge regarding surgical procedures, anesthesia, postoperative care, and safety measures may increase anxiety, reduce adherence to perioperative instructions, and contribute to postoperative complications. Digital education has emerged as an innovative strategy to provide accessible, interactive, and patient-centered health education. This literature review aimed to analyze the effectiveness of digital educational interventions in improving perioperative patient preparedness and patient safety. A literature review was conducted using articles retrieved from PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar published between 2020 and 2025. The search employed keywords including